Sound Waves and Consciousness in Saga dari Samudra: a Dialogical Study by Mikhail Bakhtin - Lailatunnuryah, Aprilia; Yuwana, Setya; Basori, NFN (SUAR BETANG, 2025)
Saga dari Samudra by Ratih Kumala is an interesting novel to study. As a fiction, this novel weaves together historical facts of life in Java in the 15th century. This article is compiled to reveal the dialogic forms between the characters, space and time, and how the novelist dialogues and negotiates with the characters he builds. Data are collected in the form of sentences and clauses, classified using Bakhtin's dialogic criteria which include chronotope, polyphony, and carnivalesque. The classified data are then coded and analyzed textually. The conclusions and meanings revealed are the results of analysis using Bakhtin's Dialogic theory. The analysis conducted leads to the conclusion that dialogue can influence power structures, moral and social norms, the anxiety of two voices in the same event but do not judge each other. Change not only reflects individual transformation, but also describes a broader social reality, such as imbalance of power, ignorance or social pressure that influences his actions in the past. The reversal of social hierarchy, two interpretations in one incident, a symbol of moral ambiguity and crossed boundaries, at the same time marking the change from victim to perpetrator, how Taksa responded by accepting what Nyai Ageng Pinatih's servant did who did not like her.